Reducing the risk of mouth-to-mouth transmission of pathogens via re-usable, machine-read parking tickets: an observational cohort study. Issue 4 (December 2017) - Groves, J.; Church, H.; Holland, D.; Thompson, N.
Summary: The car parks at the study hospital are accessed using re-usable, machine-read tickets. In the initial phase of this study, 598 staff members were observed entering the car park, and 21.6% of them put their parking ticket in their mouth. Ultraviolet dye was used to demonstrate card-to-card cross-contamination. Swabs of the ticket machine yielded commensal bacteria: coagulase-negative staphylococci and a Bacillus sp. After placing a poster on the ticket-reading machine highlighting the potential risk of infection, a further 1366 observations demonstrated a significant and persistent decline in the proportion of staff who put their ticket in their mouth ( P <0.001).